The Impact of Judicial Decisions: New Dimensions in Supreme Court-Congressional Relations, 1945-1968 - John R. Schmidhauser; Larry L. Berg; Albert Melone (Washington University Law Quarterly, 1971)
This research report is an investigation of Congressional roll call behavior and interest group activity in response to Supreme Court decisions involving civil rights and liberties, and economic, labor and welfare issues. The report is designed to explore the nature and relative stability of those variables which may influence Congressmen when they vote on judiciary-oriented roll calls in the above mentioned issue categories.